Reformasi Kebijakan Pajak dalam Kerangka Ekonomi Is-lam: Antara Zakat dan Pajak - Luli Puspita (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the potential for reforming tax policy within the framework of Islamic economics, focusing on the integration of zakat and tax in Indonesia. The problem arises from the dual burden felt by Muslim taxpayers who are obliged to pay both zakat and tax without fiscal incen- tives or proper integration. The objective is to explore a fair and efficient model that positions zakat as part of the national fiscal system. Using a qualitative descriptive-analytical method, data were col- lected through literature reviews and semi-structured interviews with experts in Islamic economics, taxation, and zakat management. The findings highlight that zakat holds significant economic potential (estimated at over IDR 200 trillion annually) but remains underutilized due to fragmented regulations and limited trust in zakat institutions. The integration model requires legal harmonization, institutional synergy (especially between BAZNAS and the Directorate General of Taxes), and digital information systems to ensure accountability. This reform not only aligns with maqashid syariah principles but also strengthens fiscal legitimacy, promotes social justice, and supports inclusive development. The study concludes that the integration of zakat and tax is not merely a technical issue but a strategic move toward a more just and faith-aligned fiscal policy.